2019
DOI: 10.1149/2.0491908jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Al Doped Polypyrrole Composite Polymer: Mott-Schottky Approximation and Density Functional Theory

Abstract: Polypyrrole and Al doped polyprrole thin films were synthesized by electrochemical deposition method. FTIR spectroscopic studies confirm the formation of PPy and Al:PPy thin films. From the FESEM crosssectional images, film thickness were measured as 393.9 and 425.0 nm for the PPy and Al doped PPy thin film, respectively. Electrochemical properties of the deposited polymers are studied by Mott-Schottky analysis and electrochemical impedance spectroscopy. The calculated acceptor concentration is 5.03 × 10 18 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Figure 7 presents the MS plots of γ-FeOOH, PPy, and PFL/CDs-2, validating the n-type with positive slope and p-type with negative slope charge characteristic nature of γ-FeOOH and PPy, respectively. 55,56 At the same time, the PFL/CDs-2 composite showed both the positive and negative slopes, which reveal the n-type and p-type semiconductor conductivity nature of the composite (Figure 7c). According to the semiconductor properties, the flat-band potential (E fb ) values of n-type and p-type semiconductors were practically located near the conduction band (CB) and valence band (VB), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Figure 7 presents the MS plots of γ-FeOOH, PPy, and PFL/CDs-2, validating the n-type with positive slope and p-type with negative slope charge characteristic nature of γ-FeOOH and PPy, respectively. 55,56 At the same time, the PFL/CDs-2 composite showed both the positive and negative slopes, which reveal the n-type and p-type semiconductor conductivity nature of the composite (Figure 7c). According to the semiconductor properties, the flat-band potential (E fb ) values of n-type and p-type semiconductors were practically located near the conduction band (CB) and valence band (VB), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Even so, there are few reports about strategies for tuning energy levels of PPy. In particular, some examples on this aspect have considered the formation of composite materials [ 61 , 62 ], the insertion of substituents into the monomer [ 63 ], and the insertion of new dopants into the polymer [ 64 ]. However, as far as we know, there are no reports on variations in the HOMO level of PPy when adjusting the electrosynthesis potential.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Alizadeh et al reported the effect of dopant on the optoelectronic properties of electro-synthesized PPy on FTO [ 71 ]. Meanwhile, for PPy electro-deposited on ITO, it has been observed that dopant modifications leads to different degrees of adhesions and energy levels [ 40 , 64 ]. Regarding temperature, it was found (using ITO electrodes) that the conductivity of PPy decreased by two orders of magnitude when the temperature was adjusted from 2 to 75 °C [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The next analysis of EIS spectra was performed using equivalent circuit represented in Fig. 8e, because in some literature sources [37][38][39][40]41 it is reported that equivalent circuits based on connected in parallel the sequence of R-C are applied for the evaluation of layers of electrochemically deposited conducting polymer layers. We also have tested and compared different equivalent circuits for some conducting polymers based layers and the best results were obtained for equivalent circuit based on in series connected R-C elements 42,43 in comparison to evaluation based on equivalent circuit consisting of single R-C elements.…”
Section: Resultsmentioning
confidence: 99%